Analisis ROI (Return on Social Investment) Program Tanggung Jawab Sosial Lingkungan PT PLN (Persero): Upaya Pemberdayaan Wanita Difable melalui Pelatihan Pembuatan Batik Bekerja Sama dengan Rumah Batik Berkah Jambi - Henny Malini; Iwan Arissetyadhi; Yanet Rustam (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
People who have disabilities, both physical and mental, are an essential component of society. And by providing support or opportunities for them, they can help create social equality and inclusion. People with disabilities are often associated with a physical identity, leading to stereotypes about their abilities, which can lead to discrimination. The Batik training program for people with disabilities is an initiative that can help improve skills, encourage social inclusion, increase empowerment, and provide employment opportunities. Measuring the value of benefits relative to investment costs used in efforts to empower disabled Women through Batik training in collaboration with House of Batik Berkah Jambi. The evaluation recommends using the Social Return on Investment (SROI) method. The return on social investment method can help measure business performance. The social performance of an ongoing SROI is considered appropriate for understanding impact investing (investment activities that aim to create a social impact), such as activities funded from the company's TJSL funds, which are expected to create a social impact on the community, especially the company's local community. The method of implementing the activities used is qualitative research because this activity is exploratory, descriptive research. Sources were selected using a purposive sampling technique. For SROI evaluation, According to the guidelines issued by the SROI Network UK organization, this research must examine six (six) stages of the SROI analysis method. These stages will include the 2023 SROI empowerment analysis disable program results, providing an SROI value of 2.47 with criteria worth pursuing. This means that PT PLN (Persero) UID S2JB generates a profitable social impact and produces a high SROI ratio.